Influencer Marketing on TikTok: A Literature Review Analysis - Azis Riu, Isma; Radjab, Irsan (Journal of Public Administration and Government, 2023)
This research aims to present a literature review analysis of influencer marketing on TikTok using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. By detailing the PRISMA steps, this study systematically explores and organizes literature related to influencer marketing on TikTok. The analysis includes the identification of resources, selection of studies meeting inclusion criteria, data extraction, as well as quality assessment and synthesis of findings. The results of this research provide a comprehensive overview of trends, strategies, and the impact of influencer marketing on TikTok, with a focus on the clarity of the methodology used. The implications of these findings are integrated into the PRISMA framework, offering a systematic and structured contribution to further understanding the role of influencer marketing in the TikTok era. The study also provides insights into potential future research within this domain using the PRISMA framework.